Kajian Pembinaan Sistem Saliran Mesra Alam di Kawasan Pembinaan Baharu - Mohamad Razip, Nursyafika; Shareh Musa, Sharifah Meryam; Zainal, Rozlin; Mohd Noh, Hamidun; Kassim, Narimah (Research in Management of Technology and Business, 2021)
Drainage system is an important factor in every new development. Drainage systems serve to control surface runoff especially in new development areas. This study aims to look at the use of Urban Stormwater Management Manual for Malaysia (MSMA) in controlling flash floods in new development areas. The first objective of the study is to identify the impact of surface runoff on the construction of environmentally friendly drainage systems in new development areas. The second objective of the study is to identify the effectiveness of building an environmentally friendly drainage system in new development areas. The impact of the opening of new development areas has led to an increase in surface runoff rates. To complete thisstudy the method used is qualitative. Qualitative used are interviews and observations related to drainage systems in new development areas. Interviews were conducted on the respondents involved in this study. Observation methods are done to see the drainage system used. The construction of environmentally friendly drainage systems can reduce surface runoff rates and flash flood phenomena. This is because, this manual is an environmentally friendly method to replace the previous drain. In conclusion, the construction of environmentally friendly drainage system in new development areas can provide a clear picture of the drainage system used in new development areas.